Pédagogie universitaire et didactique des mathématiques - Colette Picard
As a professor in teacher training, we noticed that our university students had difficulties in teaching mathematics from a socioconstructivist perspective. This can be explained, in part, by the fact that during their schooling, these students have had few experiences of this type of teaching. Their own learning in mathematics consists mostly of explanations and demonstrations. They tend to reproduce these patterns, in spite of the socioconstructivist theories they are introduced to. A teaching approach based on problem solving was used as a framework for developing a project, in partnership with two primary schools, where student teachers tutored children experiencing significant learning difficulties in mathematics. These tutorials modified the students' experiential repertoire and became a framework for planning and supervising teaching and learning activities which encourage children to construct mathematical concepts by themselves.